Molecularly imprinted polymers on the surface of magnetic nanoparticles for selective separation and detection of nucleobases - Zemánková, Kristýna; Bezděková, Jaroslava; Vodová, Milada; Vaculovičová, Markéta (Tanger, 2020)
Nucleobases are the main building blocks in DNA and RNA playing very important roles in cell metabolism. Changes of bases in DNA sequence may affect function of products of gene expression - proteins, and this can lead to inherited diseases and most human cancer types. Pharmacological studies, clinical diagnosis and others areas need a quick, inexpensive and exact method for determination of nucleobases. In this work, we explore the possibility of improving detection of nucleobases by using capillary electrophoresis in combination with isolation by magnetic particles modified by molecularly imprinted polymer.

Nucleobases are the main building blocks in DNA and RNA playing very important roles in cell metabolism. Changes of bases in DNA sequence may affect function of products of gene expression - proteins, and this can lead to inherited diseases and most human cancer types. Pharmacological studies, clinical diagnosis and others areas need a quick, inexpensive and exact method for determination of nucleobases. In this work, we explore the possibility of improving detection of nucleobases by using capillary electrophoresis in combination with isolation by magnetic particles modified by molecularly imprinted polymer.
Molecularly imprinted polymers on the surface of magnetic nanoparticles for selective separation and detection of nucleobases
Keywords: Capillary electrophoresis; nucleobases; magnetic particles; molecularly imprinted polymers; Capillary electrophoresis; nucleobases; magnetic particles; molecularly imprinted polymers